The construction project is the main subject of management - Vornichesku, O.; Shatrova, I. (Ways to Improve Construction Efficiency, 2022)
In the article, based on the analysis of literary sources, the concept of "construction organization" is defined, the logistical methods of choosing a place for the construction of a warehouse are considered, and their role in achieving strategic and current management tasks, optimizing production activities, as well as ensuring the effectiveness of cost management of enterprises is determined. Based on the results of the analysis of scientific works, it was concluded that the introduction of a value-oriented approach to the formation of project content and the use of work decomposition for construction projects is urgent and requires clarification and research. An improved approach to managing the content of construction projects is proposed, which integrates the value components of the requirements and needs of stakeholders, which are presented in the form of a work decomposition structure. Implementation of these processes will allow the project manager and his team to take informed and controlled risk on project execution in order to create value that integrates the values of stakeholders. Meeting the goals of owners and users is fundamental to creating value through the project. In order to effectively create the value of a construction project, the value of users must be aligned with the owner’s strategies, embedded in the content of the project and controlled throughout the entire life cycle of the project and its product. The project manager must be clearly aware of the consequences of not taking into account or ignoring the values of stakeholders, and how to improve or support the value attitudes of stakeholders for effective management of a construction project. It was concluded that the value-oriented management of the content of the construction project can become the basis for a new component of the methodology of project content management, which will allow to include in the content recommendations and relevant documents that regulate the values of stakeholders, and also allow monitoring at all stages of the project life cycle and control of both values and content components.